E-Catalogue Design for the Tourism Industry Using a Design Thinking as a Media to Promote Tour Packages in Indonesia - Aprilia Ferennis; Wahyuniar Pamungkas; Lintang Permata Sari Yuliadi; Asep Agus Handaka; Nur Sakinah Junirahma (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: The tourism industry requires the use of digital media in promotion, particularly due to travelers’ increasing reliance on technology. Anjani Event, as a newly established travel company, still uses PDFs as promotional media, making it necessary to implement an interactive and easily accessible solution. This study aims to design an e-catalogue as a marketing medium for tour packages and to evaluate their effectiveness. Method: The research employs a mixed-method approach with an Exploratory Sequential design, beginning with qualitative data collection through interviews with the Anjani Event manager to develop the e-catalogue concept, followed by quantitative data collection using questionnaires based on the EPIC Model (Empathy, Persuasion, Impact, Communication) administered to prospective tourists and digital marketing practitioners. Result: The results show that the e-catalogue are highly effective with an EPIC rate of 4.30, with the Communication dimension scoring the highest (4.399), indicating that the media conveys information clearly, presents content in an easily understandable structure, and enhances user interaction and engagement in exploring and booking tour packages. Contribution: Therefore, the implementation of the e-catalogue and QR Code supports a digital marketing strategy that is informative, interactive, professional, and strengthens the company’s brand image in the tourism industry.